A droplet platform capable of handling dissimilar liquids and its application for separation of bacteria from blood - Wu, Jiawei (2021)
For passive droplet generation, multiple parameters such as the fluid viscosities and flow rates of the continuous and discrete phases correlate to each other, raising relevant control difficulties. In the current study, a droplet platform that is capable of handling dissimilar liquids is proposed. Through combining oscillatory flow and electric charge, synchronized generation and forced coalescence of different droplets can be achieved. Its application for the separation of E. coli from blood is tested, which leads to a high capture efficiency with less sample and within a shorter time than usual.